Effectiveness of Ritonavir-Boosted Protease Inhibitor Monotherapy in Clinical Practice Even with Previous Virological Failures to Protease Inhibitor-Based Regimens. - Luis F López-Cortés (PLoS ONE, 2016)
BACKGROUND AND OBJECTIVE:Significant controversy still exists about ritonavir-boosted protease inhibitor monotherapy (mtPI/rtv) as a simplification strategy that is used up to now to treat patients that have not experienced previous virological failure (VF) while on protease inhibitor (PI) -based regimens. We have evaluated the effectiveness of two mtPI/rtv regimens in an actual clinical practice setting, including patients that had experienced previous VF with PI-based regimens. METHODS:This retrospective study analyzed 1060 HIV-infected patients with undetectable viremia that were switched to lopinavir/ritonavir or darunavir/ritonavir monotherapy. In cases in which the patient had previously experienced VF while on a PI-based regimen, the lack of major HIV protease resistance mutations to lopinavir or darunavir, respectively, was mandatory. The primary endpoint of this study was the percentage of participants with virological suppression after 96 weeks according to intention-to-treat analysis (non-complete/missing = failure). RESULTS:A total of 1060 patients were analyzed, including 205 with previous VF while on PI-based regimens, 90 of whom were on complex therapies due to extensive resistance. The rates of treatment effectiveness (intention-to-treat analysis) and virological efficacy (on-treatment analysis) at week 96 were 79.3% (CI95, 76.8-81.8) and 91.5% (CI95, 89.6-93.4), respectively. No relationships were found between VF and earlier VF while on PI-based regimens, the presence of major or minor protease resistance mutations, the previous time on viral suppression, CD4+ T-cell nadir, and HCV-coinfection. Genotypic resistance tests were available in 49 out of the 74 patients with VFs and only four patients presented new major protease resistance mutations. CONCLUSION:Switching to mtPI/rtv achieves sustained virological control in most patients, even in those with previous VF on PI-based regimens as long as no major resistance mutations are present for the administered drug.